Selective solid-phase extraction of metal for water decontamination - Mane, Sachin; Ponrathnam, Surendra; Chavan, Nayaku (Journal of Applied Polymer Science, 2016)
Metal-contaminated industrial effluent is a major concern for human health. Therefore, the removal of metal is of primary importance. In this study, metals were selectively extracted from water. Selective metal recovery was studied with a crown-ether-based polymer, wherein the selectivity was observed for strontium over lead. Parameters influencing the metal recovery, such as the contact time, adsorbent dosage, and metal-ion concentration, were evaluated. Interestingly, the adsorption rate of strontium was exponentially increased for the initial 4 h, and lead was adsorbed exponentially after 6 h. Notably, 98% strontium adsorption and 64% lead adsorption were obtained in 24 h. The Langmuir adsorption isotherm was in good agreement and demonstrated that the reactive sites of the adsorbent were homogeneous with monolayer metal adsorption with an adsorbent. The Freundlich adsorption isotherm was not obeyed by both metals. The pseudo-first-order and pseudo-second-order kinetics indicated that strontium was adsorbed by chemisorption and lead was adsorbed by physisorption. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 132, 42849.
Keywords: Adsorption; copolymers; crosslinking; kinetics; radical polymerization